Diet Overlap and Predation Between Largemouth Bass and Walleye in Wisconsin Lakes Using DNA Barcoding to Improve Taxonomic Resolution. (26th May 2016) - Kelling, Craig J.; Isermann, Daniel A.; Sloss, Brian L.; Turnquist, Keith N.
Abstract: Over the last decade, the abundance of Largemouth Bass Micropterus salmoides has increased in many northern Wisconsin lakes, causing concern among anglers and biologists regarding the potential for Largemouth Bass to negatively affect populations of Walleye Sander vitreus through predation or competition for prey. Our objectives were to determine whether (1) diet overlap and predation occurred between adult Walleyes and Largemouth Bass in four northern Wisconsin lakes and (2) the use of DNA barcoding to reduce unidentifiable fish in diet samples affected conclusions regarding diet overlap. A single occurrence of Walleye predation was observed in the diets of 945 Largemouth Bass. Moderate to high diet overlap was observed between Largemouth Bass and Walleyes throughout much of the study period. The use of DNA barcoding reduced the amount of unidentified fish in diets to <1% and showed that failure to identify fish or fish parts can affect conclusions regarding diet overlap. Largemouth Bass predation is probably not a primary factor affecting Walleye abundance in the lakes we selected, but observed diet overlap suggests the potential for competition between the two species. Received June 15, 2015; accepted January 18, 2016 Published online May 26, 2016